Les enjeux de la communication de l’économie solidaire en Île-de-France - Cyrille Terrier (Communication)
This study is based on field interviews in order to single out communication problems specific to economies of solidarity in the Ile-de-France and to put forward solutions. Several areas of concern were identified, among them, localisms, discourse semantics and the integration of new technologies in communication strategies. The analysis highlights the understanding that the participants have of their own communication quandary, caught between the wide broadcasting opportunities offered by the media, the will to control content and the relevance of staying in touch with local roots.